A formação de professores em modelagem matemática: considerações a partir de professores egressos do programa de desenvolvimento educacional do Paraná - PDE - Tambarussi, Carla Melli (2015)
The research related to the teachers education Modeling is relatively recent in the context of research in Mathematical Modeling, with the first investigation carried out in 2001, as revealed a work developed by us. In addition, this work has shown the absence of dissertations and theses that have dedicated themselves to study the later time the involvement of teachers in continuing teachers education activity. Thus, intentionally directed to the phenomenon: Mathematical Modeling continuing teachers education, established the following research question: What is revealed about Mathematical Modeling teachers education from teachers graduates of the PDE, that addressed the Modeling in your projects implementation? The assumed research methodology is qualitative according to the phenomenological approach, which seeks to show the phenomenon as it turns out, without theoretical frameworks previously established. In this research attitude, the question leads all research, so we seek teachers who participated in the PDE and developed the implementation project under the theme of Mathematical Modeling. From this search, ten teachers have proved capable of being investigated, of wich two teachers no longer worked in the classroom. The eight other teachers are collect the testimonials and observe, when allowed, their classes. With the data in hand, we analyze the process that took place with the help of Atlas t.i. software. This process was conducted by the research question and aimed to detach the units of meaning that emerged from reports (which were transcribed) and the observations of classes. After the analyzing we spent interpreting process, which was conducted hermeneutically. For each teacher conducted an interpretation, which revealed aspects related to PDE; the teachers Modeling conception; the teachers education conception; the teaching practice; students and Modeling; the curriculum; the implementation project and what was shown about the Modeling teachers education of the teachers who participated in the PDE and implemented this trend in their projects. Besides presenting interpretations individually, in the last chapter we seek to articulate the categories that emerged from the data of each teacher made explicit and other aspects about the teachers education Modeling. Among these aspects, it was revealed that teachers education Modeling of the teachers who have implemented their trend in the projects proved fragile and had no effective contributions to the work in the classroom. In addition, there is the superficiality with which the Modeling was discussed during the PDE, and the timeliness of this program in terms, for example, the courses offered and the orientation process. Thus, reveals that one of the modeling community needs to propose differing Modeling teachers, from those already established, that is, focusing on traditional aspects, which are based on the discussion of texts and do not provide a teachers education that is, in fact, continued.